CAUSES ET CONSEQUENCES DU CHOMAGE DES CADRES UNIVERSITAIRES DANS LA VILLE DE KISANGANI. - ASAKA John, ANGONDO; Felix ELANGA ATILAMBISA; Jadis SENGA YENGA; Jean ANDRIOZI OMBA; Salthiel BOYEMBA AYOMBA; Emmanuel LOMBO ILONGE; Ivette NYALUSALA IKANDO (IJRDO - Journal of Social Science and Humanities Research, 2019)
The present survey has for preoccupation to identify the reasons that are to the basis of the unemployment of the academic settings in the city of Kisangani; to clear the problems that the academic youngsters meet when they look for a job and to show the consequences of the unemployment of academic settings to Kisangani. To achieve this survey us made resort to the dialectic method. To the descended of the investigation, we noted that the reasons that are to the basis of the unemployment of the academic settings are the lack of uses disponibleset professional inaptitude of some academic settings, the inability of the state to reprocess the agents and eligible civil servants to the pension of retirement, the absence of the politics of creation of employment by the state, the cost of academic settings, the lack of mind of entreprenariat and the refusal to work in the farming surroundings. Besides the problems that the academic settings meet are the next one: the tribalisme, the corruption and political adherence as well as the knowledge of English and the mastery of the computer tool. And finally, the consequences are the culture of poverty, the proliferation of criminality, the rate raised of mortality and prostitution, the démotivation to pursue the academic studies, the lack of access to the social services of basis and the occupation of all employment not matching the path of survey. Indeed, to the look of the size of number of the unemployed person in Democratic Republic of Congo in general and in the city of Kisangani the Congolese state must create the jobs in particular, in all domains of the national life in view of to recruit the academic youngsters and to resort to the quota as in the past at the time of the enrollments of the studying candidates in every path.